Exploring Kindergarten Students' Early Understandings of the Equal Sign. Issue 3 (3rd July 2018) - Blanton, Maria; Otálora, Yenny; Brizuela, Bárbara M.; Gardiner, Angela Murphy; Sawrey, Katharine B.; Gibbins, Aliska; Kim, Yangsook
ABSTRACT: This study explores kindergarten students' early notions of mathematical equivalence in the United States. In particular, it uses qualitative methods to examine the understandings children hold about the equal sign prior to formal instruction and how these understandings shift throughout an 8-week classroom teaching experiment designed to develop relational thinking about this symbol. Findings suggest that, even prior to formal instruction, young children hold an operational view of the equal sign that can persist throughout instruction. This early and persistent operational perspective underscores the critical need to design mathematical experiences in kindergarten, and even preschool, that will orient students towards a relational understanding of the equal sign upon its introduction in first grade.